L’enseignement commercial « prisonnier de la forme scolaire » (1870-1905) ? - Marianne Blanchard (Les Cahiers de Framespa)
This paper focuses on teaching in the first business schools (écoles supérieures de commerce) in 19th-century France and analyzes to what extent the development of formal schooling in business has constrained the teaching methods implemented in this area of knowledge. The first part of the text deals with the difficult emergence of business education in the early 19th century, formal education in this domain being then considered as useless. The case of Ecole supérieure de commerce de Paris, founded in 1819, illustrates these difficulties, but also the hesitations over the most appropriate teaching methods to provided efficient courses but also gain academic legitimacy. The second part of the text considers more precisely the “commercial bureau” (game simulation) method of teaching that was notably implemented in the Ecole supérieure de commerce in Mulhouse (1866-1872).